KEGIATAN EKSRAKURIKULER KEROHANIAN ISLAM DALAM MENGEMBANGKAN WATAK KEWARGANEGARAAN PESERTA DIDIK - Wika Hardika Legiani, Ria Yuni Lestari, (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
This Study discusses of extracurricular activities in developing civic disposition of students of SMAN 12 Semarang. The purpose of this study is to obtain an overview Islamic spirituality programs of the civic disposition developed in the extracurricular activities these activities become the provision of students to live in society. The approach used in this study is qualitative approach with case study method. The collecting of the data is by using observation, interview. The findings of the study are process of ROHIS extracurricular activities in developing characters of citizenship include polite,respect for peoples,obey the law, honest, open mind, critical thinking, compromise, mercy, persistent, patriotsm, bravery, tolerance. This can be formed through routine activities carried out by Islamic spiritual extracurricular activities likes routine study every week, social service, commemoration of religious holidays like Isra Miraj, Mulid Nabi, Eid al-Adha prayer. It can provide provisions for students to be able to have good morals which will be used as provisions in community life, so that they will be very useful individuals for the surrounding environment.Keyword:Extracurricular, Islamic Spiritual Extracurricular, Civic Disposition